2009
DOI: 10.1158/1055-9965.epi-08-1133
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Acrylamide Intake and Brain Cancer Risk

Abstract: Background: Acrylamide is a probable human carcinogen, which is present in several heat-treated foods. In epidemiologic studies, positive associations with endometrial, ovarian, and renal cell cancer risk have been observed. The incidence of central nervous system tumors was increased upon acrylamide administration in drinking water to rats. In the current study, the association between dietary acrylamide intake and human brain cancer risk was investigated for the first time. Methods: In 1986, 120,852 persons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 13 publications
0
28
0
2
Order By: Relevance
“…These DNA adducts cause depurinating lesions, and the repair of these lesions can also lead to the formation of DNA breaks (Friedberg et al, 1995;Martins et al, 2007). In a study that followed human subjects for a period of 13.3 years, a positive association between dietary acrylamide and renal cell cancer risk was found (Hogervorst et al, 2008), and increasing incidences of endometrial, ovarian, and renal cancer with increased dietary ACR intake have also been reported (Hogervorst et al, 2009). Moreover, ACR-induced neurological symptoms followed by neuropathy have been reported in a cohort study of occupationally exposed workers (He et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…These DNA adducts cause depurinating lesions, and the repair of these lesions can also lead to the formation of DNA breaks (Friedberg et al, 1995;Martins et al, 2007). In a study that followed human subjects for a period of 13.3 years, a positive association between dietary acrylamide and renal cell cancer risk was found (Hogervorst et al, 2008), and increasing incidences of endometrial, ovarian, and renal cancer with increased dietary ACR intake have also been reported (Hogervorst et al, 2009). Moreover, ACR-induced neurological symptoms followed by neuropathy have been reported in a cohort study of occupationally exposed workers (He et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary minerals, especially calcium and zinc, have protective effects against tumors, including gliomas (68,69). No correlation between acrylamide, present in several heat-prepared foods and glioma risk was found by a study (70).…”
Section: Lifestyle Factorsmentioning
confidence: 94%
“…The earliest epidemiological studies have failed in finding an association between acrylamide dietary intake and an increased risk of cancer whereas some of the latest epidemiological studies have reported an increased risk for some kinds of cancer. Up to date, the outcomes of these epidemiological studies agree in indicating no positive association between total dietary acrylamide intake and risk of colorectal cancer (Hogervorst, Schouten, Konings, Goldbohm, & van den Brandt, 2008a;Larsson, Kesson, Bergkvist, & Wolk, 2009;Mucci, Adami, & Wolk, 2006;Mucci, Dickman, Steineck, Adami, & Augustsson, 2003;Pelucchi et al, 2006), bladder cancer (Hogervorst, Schouten, Konings, Goldbohm, & van den Brandt, 2008b;Mucci et al, 2003), esophageal cancer (Hogervorst et al, 2008a;Pelucchi et al, 2006), prostate cancer (Hogervorst et al, 2008a;Larsson, Akesson, & Wolk, 2009b;Pelucchi et al, 2006;Wilson et al, 2008), oropharyngeal (Pelucchi et al, 2006), laryngeal (Pelucchi et al, 2006), pancreatic (Hogervorst et al, 2008a), gastric (Hogervorst et al, 2008a) and brain cancer (Hogervorst, Schouten, Konings, Goldbohm, & van den Brandt, 2009a). For renal cell cancer, ovarian cancer, and breast cancer, the results from epidemiological studies are conflicting.…”
Section: Epidemiological Datamentioning
confidence: 99%